Development of HOGU as Digital Storybook for Islamic Education in Elementary School - Ani Nur Aeni; Dadan Djuanda; Nurdinah Hanifah; Nabilah Nur Apriyanti; Qasthalani Yasmin; Syakira Aulia Karima (Ta'dib, 2024)
a major challenge faced in the world of education today is the lack of student interest and motivation in the learning process. One of the efforts to increase student learning motivation is to see how the role of educators in schools in providing teaching to students. In providing teaching in the classroom, teachers can use learning media as an alternative in delivering material or information about learning. Therefore, the manufacture of products in this study aims to create a solution in increasing student learning motivation in PAI subjects in grade IV SD. This study aims to develop and test the effectiveness of a Canva-based digital storybook entitled 'HOGU' in fostering respect for parents and teachers among fourth grade elementary school students. With this HOGU (Respect for Parents and Teachers) Digital Storybook, it is hoped that it can foster respect for parents and teachers and can be applied in everyday life. This digital storybook received positive responses, with 95% of teachers and 91% of students stating its effectiveness in increasing respect for parents and teachers. This research shows that Canva-based digital storybooks can effectively engage primary school students and reinforce moral teachings in Islamic education. This Digital Storybook is designed in an attractive and easy-to-understand language for students. This research uses the ADDIE model which starts from the analysis stage to the evaluation of the product that has been created and implemented.